2020
DOI: 10.1016/j.heliyon.2020.e05118
|View full text |Cite
|
Sign up to set email alerts
|

New frozen product development from strawberries (Fragaria Ananassa Duch.)

Abstract: Strawberry fruit has a short shelf life. If stored at ambient temperature only lasts 1 day, so it needs to be dried into a frozen product so that its shelf life is longer. Frozen products are favored by consumers because they still have properties like fresh fruit. This study was aimed at examining the physical and sensory characteristics of new frozen products from strawberries. The research sample was freeze-dried at 3 variations of the heating plate temperature were 40, 50, and 60 C and 3 variations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The water content of the product is calculated by Eq. (1) below [ 32 ]: where, MC = moisture content, a = weight of empty cup, b = weight of cup + initial sample, c = weight of cup + sample after drying.…”
Section: Methodsmentioning
confidence: 99%
“…The water content of the product is calculated by Eq. (1) below [ 32 ]: where, MC = moisture content, a = weight of empty cup, b = weight of cup + initial sample, c = weight of cup + sample after drying.…”
Section: Methodsmentioning
confidence: 99%
“…The main quality parameter of dried fruit products for marketing value and consumer choice is color [4][9] [21]. The visual difference between fresh and freeze-dried strawberries from the result shown in Figure 2, the color of fresh strawberries is greenish-red and freeze-dried strawberries are maroon.…”
Section: Physical Qualitymentioning
confidence: 99%
“…The red pigment in strawberry fruit comes from the concentration of anthocyanins, with the major anthocyanin being pelargonidin 3-glucoside, with cyanidin 3-glucoside and pelargonidin 3-rutinoside present as minor components [18]. One of the color parameters that needs attention is the color of change that occurs in strawberries, because this is influenced by physiology and chemistry changes (synthesis of carotenoid and flavonoid pigments) in strawberries during the freeze-drying process [21]. The analysis revealed that the samples of pre-treatment had a higher color change value than the without pre-treatment samples.…”
Section: Physical Qualitymentioning
confidence: 99%
“…For long‐term preservation, frozen storage is a useful method that acts by slowing enzymatic damage and microbial growth (Liang et al ., 2015). Furthermore, frozen fruit products are popular with consumers today because these products still have sensory (colour, aroma, taste) and nutritional properties similar to those of fresh fruit (Ansar et al ., 2020; Orqueda et al ., 2021). However, the quality of frozen fruit continues to change during storage, and temperature fluctuations can affect quality (Zhang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%